Effects of Temporal Features and Order on the Apparent duration of a Visual Stimulus - Bruno, Aurelio; Ayhan, Inci; Johnston, Alan (Frontiers in Psychology, 2012)
The apparent duration of a visual stimulus has been shown to be influenced by its speed. For low speeds, apparent duration increases linearly with stimulus speed. This effect has been ascribed to the number of changes that occur within a visual interval. Accordingly, a higher number of changes should produce an increase in apparent duration. In order to test this prediction, we asked subjects to compare the relative duration of a 10-Hz drifting comparison stimulus with a standard stimulus that contained a different number of changes in different conditions. The standard could be static, drifting at 10 Hz, or mixed (a combination of variable duration static and drifting intervals). In this last condition the number of changes was intermediate between the static and the continuously drifting stimulus. For all standard durations, the mixed stimulus looked significantly compressed (∼20% reduction) relative to the drifting stimulus. However, no difference emerged between the static (that contained no changes) and the mixed stimuli (which contained an intermediate number of changes). We also observed that when the standard was displayed first, it appeared compressed relative to when it was displayed second with a magnitude that depended on standard duration. These results are at odds with a model of time perception that simply reflects the number of temporal features within an interval in determining the perceived passing of time.